Sosialisasi dan Pendampingan sebagai Upaya Peningkatan Kualitas Pemilih untuk Meningkatkan Efisiensi dan Efektivitas Pemilihan Kepala Daerah - Hadad, Sitna Hajar; Hairun, Radina Hamza; Nurnela, Nurnela (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2024)
Regional elections are a democratic process that provides an opportunity for the people of a region to directly elect their leaders. This process is an important milestone in a country's political system at the local level, where voters have the power to choose figures deemed capable of representing and leading their region towards better progress and prosperity. Assistance in regional elections is a strategic effort to improve the quality of voters with the ultimate goal of increasing the efficiency and effectiveness of the entire election process. The results of the level of understanding of the activities that took place in the Bimtek activities for regional head elections showed a positive impact in improving participants' understanding and skills related to the regional head election process. Based on the evaluation conducted, the results showed a significant improvement in participants' understanding of various aspects of the election, including legal procedures, implementation techniques, supervision, and dispute resolution. Bimtek participants showed an increased clear understanding of their roles and responsibilities in regional elections. They become more skilled in planning and managing the electoral process, including logistical arrangements, voting procedures, and reporting results.